Cover Image, Volume 529, Issue 8. Issue 8 (29th March 2021) - Grob, Robin; Tritscher, Clara; Grübel, Kornelia; Stigloher, Christian; Groh, Claudia; Fleischmann, Pauline N.; Rössler, Wolfgang
Abstract : The cover image is based on the Research Article Johnston's organ and its central projections in Cataglyphis desert ants by Robin Grob et al., https://doi.org/10.1002/cne.25077 .